Case Report: Lymphodepletion followed by CAR-T cell therapy with Idecabtagen vicleucel in a patient with severe renal impairment - Marquard, Franziska; Langebrake, Claudia; Janson, Dietlinde; Mahmud, Maida; Dadkhah, Adrin; Kröger, Nicolaus; Ayuk, Francis (Frontiers in Oncology, 2023)
Acute kidney injury and chronic kidney disease is common in multiple myeloma. Fludarabine which is part of lymphodepletion before CAR-T cell therapy is renally eliminated and its use is not recommended for patients with severe renal impairment defined as a glomerular filtration rate below 30ml/min/1.73m 2 . We administered fludarabine to a 58-year-old female patient with myeloma-associated severe renal impairment as part of lymphodepletion before Idecabtagen vicleucel infusion. Fludarabine was administered in reduced dose (15mg/m 2 ) and cyclophosphamide with a dose of 300mg/m 2 followed by hemodialysis over six hours using a larger filter (FX-100). The therapy was well tolerated with excellent CAR-T cell expansion and complete remission which is ongoing now beyond 12 months.